Reflections on the expansion of the scope of agricultural law regulation – a notary’s perspective - Blajer, Paweł A. (Przegląd Prawa Rolnego, 2021)
The aim of the research conducted within the framework of this paper was to characterise the expansion of the scope of regulations classified as agricultural land law, resulting from the amendment to the Act on shaping the agricultural system of 2016, and its impact on the notarial practice of real estate trading. In the first part of the study, general issues presenting the scale of the impact of this Act on the regulations hitherto free from any form of “agrariarisation” (in particular, the traditional institutions of civil law, civil proceedings, company law and bankruptcy law) were analysed. In the second part of the paper, a practical dimension of the Act has been illustrated by an analysis of the problems that notaries as practitioners face when applying it in their everyday work. As part of the concluding remarks, an assessment of the expansion of the agricultural law regulation in the Polish legal system has been made, demonstrating that this process does not occur in a rational and coherent way.